Description of The Level of Knowledge of Basic Life Support (BlS) With Readiness To Perform Bhd Actions on Anesthesiologists - Nurul, Nurul Hidayati; Burhan, Asmat; Nova Handayani, Rahmaya (Java Nursing Journal, 2025)
Background: Cardiac arrest is one of the significant risks among those associated with surgery, interventional procedures, or anesthesia. Basic life support (BLS) is the immediate action taken in critical or emergency situations to save lives. The health care personnel must possess adequate knowledge and ability to handle such emergencies effectively. Anesthesiologists must necessarily be BLS proficient to give an early intervention during emergencies just like any other medical professional. Purpose: This study will evaluate the knowledge and preparedness of BLS among the anesthesiologists of the Central Surgical Installation in Banyumas Regency. Methods: The study used a cross-sectional design. Data were collected using surveys dispatched online to the 47 participants through Google Forms from June 19 to 28, 2024, in Banyumas Regency. Results: The results showed that 32 participants (72.3%) possessed excellent knowledge of BLS; however, 24 of 47 responders (51.1%) felt that they were adequately prepared for BLS action when needed. Conclusion: The study disclosed a positive correlation between BLS knowledge and preparedness to perform BLS among anesthesiologists in the Banyumas Regency, thus stressing continuing education and training to promote preparedness in case of emergencies